The Construction of Ideological Subjects: Siamese Students in Anna Leonowens' English Classroom. Issue 3 (3rd July 2019) - Tripasai, Pornsawan
ABSTRACT: The history of English language teaching in Thailand is recorded in Anna Leonowens' Orientalist text. In 1862, Leonowens came to Siam to work as an English teacher for King Mongkut's children. She retired from her teaching position and left the country in 1867. Leonowens wrote an account of her experience in Siam, publishing it under the title The English Governess at the Siamese Court in 1870. Similar to other Orientalist texts about the East, Leonowens' story of Siam is imbued with the Orientalist representation of the Orient. Siamese students are described as benighted Orientals who, under the English teacher's guidance, are transformed into noble savages. The transformation process is reflected in the author's depiction of her English classroom as a contested site of conflict between Siamese and Western ideologies, which finally gives way to the triumph of Western ideology. The purpose of this article is to explore how Leonowens' Orientalist representation powerfully constructs Siamese students as ideological subjects. Although Leonowens' text is set in nineteenth century Siam, it can be used as a metaphor to make understandable Thai students' internalisation of Western ideology that gains their consent and directs their mind to the West.